(untitled) (Journal of Educational Sciences, 2020)
Now in the countries of the world an actual problem becomes preparation of the qualified, talented, competitive experts who continuously develop in various branches of science and education, from year to year technologies are updated, introduced into the industrial branch. In this regard, changes and additions to the legislation of the country’s education system are made from year to year. There fore, an important role in providing in-depth knowledge of future specialists in our country is played by many effective methods of training in the educational process. The article offers methods of formation of research activity of students. The study of biology shows the division of students into groups in the formation of business activities of students and the implementation of jointly proposed project research sessions “Determination of biologically active substances of vegetative organs of plants.” Defining, forming, controlling, analytical levels of lessons of project research are described, efficiency of formation of research competence of future specialists-biologists as a result of research activity on this level is characterized. The result of joint activities is a group final product, which is often in the form of a report. The result of this work-high cognitive and educational motivation of students in the development of research and search activities-provides an increase in the creative efforts of the teacher. The results of a survey of 40 students based on the outcome of the use of research methods of training are presented in the article. The result of using the method is a high cognitive and learning motivation of students in the development of research and search activities, which provided the development of creative skills of both students and teachers. Key words: Research activity, group training, project, laboratory work, plants, biologically active substances.